Thinking About Dementia - Leibing, Annette; Cohen, Lawrence (Rutgers University Press, 2021)
Bringing together essays by nineteen respected scholars, this volume approaches dementia from a variety of angles, exploring its historical, psychological, and philosophical implications. The authors employ a cross-cultural perspective that is based on ethnographic fieldwork and focuses on questions of age, mind, voice, self, loss, temporality, memory, and affect.